TOC IMPLEMENTATION FOR MULTI-PROJECT ENVIRONMENT -A case study in ABB Distribution Automation - Nurmela, Jukka Tapani (My University, 2005)
Efficient project management is essential for the organizations. Rapid developments in the technology business create demands for management. Project organizations can respond to increased competition by efficient project management. ABB Distribution Automation decided to implement TOC-method (Theory of Constraint) for new product development projects. This Master Thesis explains how TOC-method should be used and ABB’s way to implement and utilize TOC-method in project management. This study is presented as a single case study. The theoretical part of this study explains philosophy behind TOC-method. TOC-method’s opportunities for the single- and multi-project management are presented based on top-rated TOC-literature. The purpose of the theoretical part is to give an overall picture of TOC-based project management. TOC-method is a philosophy rather than set of techniques and tools, this is the reason for detailed explanations in theoretical part. General project management dilemmas are explained and solved from TOC point of view. TOC project management solutions from the literature are the base for the empirical part of this study. Empirical part of this study explains ABB’s TOC-implementation phases and solutions for single– and multi-project management. Participating observation has been a great part of this study, because author of this study has participated full time for the TOC-method implementation and has been part of the daily multi-project management. Open interviews and statistical evaluation has been used to give essential information for the study. Study has characteristics of quantitative-qualitative research. Used methods have given practical approach for this study. During this study six projects were completed on time by using TOC-method. Delays in a projects’ completion were the biggest reason for the TOC-method implementation in a ABB. This study gains additional value, because theory has been used in a practice and practice has proved that TOC-method has improved case company’s multi-project management. KEYWORDS: Theory of Constraints, Project management, case study TIIVISTELMÄ VAASAN YLIOPISTO Teknillinen tiedekunta Tekijä: Jukka Nurmela Tutkielman nimi: TOC IMPLEMENTATION FOR MULTI-PROJECT ENVIRONMENT -A case study in ABB Distribution Automation Ohjaaja: Tauno Kekäle Tutkinto: Kauppatieteiden maisteri Laitos: Sähkötekniikan ja tuotantotalouden laitos Oppiaine: Tuotantotalous Opintojen aloitusvuosi: 1999 Tutkielman valmistumisvuosi: 2005 Sivumäärä: 118 TIIVISTELMÄ Teknologian nopea kehitys asettaa vaatimuksia yrityksille. Tehokas projektijohtaminen on edellytys projektiorganisaatioden kilpailukyvylle. Projektiorganisaatiot voivat parantaa kilpailukykyään tehokaalla projektijohtamisella. ABB:n Sähkönjakeluautomaation yksikkö päätti ottaa TOC-menetelmän (Theory of Constraint) käyttöön tuotekehitysprojektien hallintaan. Tämä tutkimus kuvaa miten TOC-menetelmää tulisi hyödyntää moniprojektiympäristössä ja miten menetelmä on otettu käyttöön ABB:lla. Lisäksi tutkimuksessa annetaan kehitysideoita miten TOC-menetelmän voitaisiin ABB:llä kehittää tulevaisuudessa. Tämä tutkimus on toteutettu yksittäisenä case-tutkimuksena. Teoreettinen osa tätä tutkimusta selventää TOC-menetelmän filosofiaa. TOC-menetelmän mahdollisuudet yksittäisten projektien ja moniprojektiympäristön hallintaan selvennetään kirjallisuuden pohjalta. Teoriaosuuden tarkoitus on antaa kokonaiskuva TOC-menetelmästä ja sen sovelluksista projektinhallintaan. TOC-menetelmä on enemmänkin filosofia kuin kokoelma erityisiä tekniikoita ja työkaluja. Siksi teoriaosa on laaja ja antaa tarkan kuvauksen TOC-menetelmästä. Yleiset projektinhallintaan liittyvät ongelmat käydään läpi ratkaisuineen. Kirjallisuudessa kuvatut menetelmät antavat lähtökohdan tutkimuksen empiriselle osuudelle. Empiirisessä osassa selvennetään TOC-menetelmän käyttöönottoa ja hyödyntämistä ABB:lla. Tutkimusmenetelmänä on käytetty enimmäkseen osallistuvaa havainnointia, koska tutkijan oma osuus TOC-menetelmän käyttöönotossa on ollut merkittävä. Tutkimusta on tarkennettu myös avoimilla haastatteluilla sekä tilastollisilla analyyseilla. Kvalitatiivis-kvantitatiivisella lähestymistavalla tutkimukseen on saatu käytännön läheinen näkökulma. Tutkimuksen aikana kuusi projektia, joissa käytettiin TOC-menetelmää, valmistui aikataulussa. Projektien viivästyminen oli suurin syy TOC-menetelmän käyttöönotolle ABB:llä. Painoarvoa tutkimukselle antaa se, että teoriaa on sovellettu käytäntöön ja TOC-menetelmän toimivuus käytännössä on todistettu case-yrityksessä. AVAINSANAT: Theory of Constraint, projektinhallinta, case-tutkimus
Keywords: Theory of Constraints; project management; case study; fi=Tuotantotalous|en=Industrial Management|